Association of neutrophil morphology with bacterial isolates in equine tracheal wash samples. (17th April 2018) - Jocelyn, N. A.; Wylie, C. E.; Lean, M.; Barrelet, A.; Foote, A. K.
Summary: Background: Tracheal wash sample neutrophilia is common in lower airway inflammation of various causes; however, relevance of cytomorphological features to culture of bacterial pathogens has not been established. Objectives: To investigate whether the presence of nondegenerate or degenerate neutrophils in tracheal washes is associated with culture of bacteria and, if so, whether this is influenced by age or temporal factors. Study design: Cross‐sectional study. Methods: Tracheal wash samples submitted to Rossdales LLP from 1/1/2013 to 31/7/2015 were evaluated using set criteria. Neutrophilia and degenerate neutrophilia (graded ≥2/4 on Rossdales cytological scale [0–4]) were analysed in relation to bacterial isolates considered potentially pathogenic in respiratory disease. Statistical analyses included multivariable logistic regression to identify associations between two separate outcomes: 1) the presence of neutrophilia compared with no neutrophilia and 2) the presence of degenerate neutrophilia compared with nondegenerate neutrophilia and four independent variables. Results: Sufficient data for inclusion in the multivariable model for nondegenerate neutrophilia were available from 1100 horses. Culture of potentially pathogenic bacteria was associated with increased odds of degenerate neutrophilia compared with samples with negative culture (OR 4.5, 95% CI 3.1, 6.4, P‐value<0.001). Horses over 9 years old had lower odds of having degenerate neutrophilia than those aged 1–3 years (OR 0.6, 95% CI 0.4, 0.9, P‐value<0.02). In the spring/summer, horses had reduced odds of a degenerate neutrophilia compared with winter (OR 0.4, 95% CI 0.3, 0.7, P‐value <0.001). Main limitations: The study relied on routine laboratory submissions, with no control over sample collection or submitted clinical history. Conclusions: Cytological evaluation of tracheal washes should include cytomorphological features of the neutrophil response. The presence of degenerate neutrophils, especially in young horses, indicates added value of culture and sensitivity for antimicrobial therapeutics. The absence of degenerate changes, in combination with clinical factors, can help support diagnosis of a nonseptic cause of airway neutrophilia.